MEMBACA DAKWAH SUFISTIK DALAM PRODUK BUDAYA POPULER (KAJIAN SEMIOTIKA TERHADAP LIRIK LAGU DEKENGANE PUSAT) - Maskuro, Vina Lailatul (Universitas Islam Negeri Imam Bonjol Padang, 2024)
Music is not only used as a medium of entertainment, but along with the development of the age music is also used as a medium of da'wah by the preachers. There are many music whose lyrics contain da'wah messages, among popular music that contains da'wah messages is the song